2017
DOI: 10.7575/aiac.alls.v.8n.2p.55
|View full text |Cite
|
Sign up to set email alerts
|

Fostering EFL Learners’ Reading Comprehension: Animation Film Technique

Abstract: The current study investigated the effect of implementing animation films on developing reading comprehension texts among EFL learners of a language institute in Kerman. For this purpose, two groups of pre-intermediate EFL learners were chosen (30 participants in each group). After three months of instruction, twice a week, 2story books named the "Good Dinosaur" and "Little Prince" including totally 20 chapters in both groups and animation films including 60 minutes divided into 6 to 7 minutes in each session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Upin and Ipin are also culturally contextual and can be explored in vocabulary and narrative discourse instruction (Moghadam et al, 2012). Animated film techniques improve students' reading comprehension (Torabian & Tajadini, 2017). It is beneficial for students in understanding reading texts based on the results of interviews (Torabian & Tajadini, 2017).…”
Section: Film Animation In Language Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…Upin and Ipin are also culturally contextual and can be explored in vocabulary and narrative discourse instruction (Moghadam et al, 2012). Animated film techniques improve students' reading comprehension (Torabian & Tajadini, 2017). It is beneficial for students in understanding reading texts based on the results of interviews (Torabian & Tajadini, 2017).…”
Section: Film Animation In Language Teachingmentioning
confidence: 99%
“…Animated film techniques improve students' reading comprehension (Torabian & Tajadini, 2017). It is beneficial for students in understanding reading texts based on the results of interviews (Torabian & Tajadini, 2017). This technique increased a higher score in students' reading comprehension (Torabian & Tajadini, 2017).…”
Section: Film Animation In Language Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research used DCT as a theoretical framework to analyze effects of visualization in foreign language learning such as vocabulary acquisition (e.g., Shalmani, 2010) and reading comprehension (e.g., Huang, 2019;Roohani et al, 2015). Researchers applied DCT in various learning contexts including comic book reading (Roozafzai, 2012), multimedia-based learning (Karbalaei & Zare, 2019;Torabian & Tajadini, 2017), and picturebooks reading (Hashemifardnia et al, 2018). Nevertheless, participants in these studies are either teenagers or adults.…”
Section: Dual Coding Theorymentioning
confidence: 99%
“…TED talks are also a valuable material in increasing the students' reading comprehension skills. The recent studies of Hayikaleng, Nair and Krishnasamy (2016), Torabian and Tajadini (2017), Metruk (2018) investigated the effects of using authentic videos on EFL reading comprehension among vocational and university students, which indicated a significant achievement in reading comprehension of the experimental group compared to the control group. Results suggested that authentic videos might be considered as an effective instructional tool for improving English reading comprehension and as an important teaching resource in English classrooms.…”
Section: The Benefits Of Ted Talks For Efl Teachingmentioning
confidence: 99%